Sistem Picking dan Packaging Menggunakan PLC Outseal dan Robot Magician - Tugino; Ahmad Dwi Indra Buana; Mohammad Arsyad; Hasta Kuntara (Retii, 2022)
Picking is the process of moving an object while packaging is the process of packing the object. The development of industrial automation systems 4.0 allows both processes to be carried out using a Programmable Logic Controller (PLC) and robots. However, most industries in Indonesia are still using human labor. This method is considered less effective because human can feel tired and bored. This study aims to make the prototype of a picking and packaging system using PLC and robots. Robot 1 plays role in loading objects, robot 2 plays role in sorting, arranging, and packing objects, while robot 3 plays role in putting the lid on the packaging. System is made using 3 Dobot Magician robots, 3 conveyors, and 1 Outseal Nano V.4 PLC. System communicates with each other through an intermediary circuit using the PIC817 IC optocoupler. The results of the study experiment carried out showed that the system worked well and as desired, the system can move objects from the point where they placed, then sort objects by color to pack. Green objects will be packed while other colors will be returned. When the package is full, the system carries away it to be given the lid on the packaging